Care in Europe after presenting to the emergency department with a seizure; position paper and insights from the European Audit of Seizure Management in Hospitals. (7th May 2022) - Taylor, Claire; Tudur‐Smith, Catrin; Dixon, Pete; Linehan, Christine; Gunko, Aleksei; Christensen, Jakob; Pearson, Mike; Tomson, Torbjorn; Marson, Anthony
Abstract: Background and purpose: This position paper makes recommendations following an audit of care provided to people presenting with a seizure to emergency departments (EDs) in Europe. Methods: Participating countries were asked to include five hospitals agreeing to identify 50 consecutive seizure patients presenting to their ED between 1 August 2016 and 31 August 2017. Anonymous data were collected to a web database. Where quoted, percentages are mean site values and ranges are the 10th–90th centile. Results: Data were collected on 2204 ED visits (47 sites, up to six per country, across 15 countries): 1270 (58%) known epilepsy, 299 (14%) previous blackouts but no epilepsy diagnosis, 634 (29%) with a first seizure. Wide variability was identified for most variables. Of those with known epilepsy, 41.2% (range 26.2%–59.6%) attended the ED in the previous 12 months, but only 64.7% (range 37.2%–79.8%) had seen an epilepsy specialist in the previous 12 months. 67.7% (range 34.0%–100%) were admitted, 53.1% to a neurology ward (range 0.0%–88.9%). Only 37.5% first seizure patients (range 0.0%–71.4%) were given advice about driving. Conclusions and recommendations: It is recommended that in Europe guidance is agreed on the management and onward referral of those presenting to the ED with a seizure; a referral process is created that can be easily implemented; it is ensured that the seizure services receive referrals and see the patients within a short time period; and a simple system is developed and implemented to allow continuous monitoring of key indices of epilepsy care. Abstract : The European Audit of Seizure Management in Hospitals (EuroNASH) shows that there is considerable and unacceptable variability in the quality of care provided to people presenting to emergency departments with a seizure in Europe. In this position paper it is recommended that in Europe (1) guidance is created and agreed for specialist referral; (2) a process for referral is created that is easy to do and can be incorporated into the workings of local hospitals with minimal effort; (3) it is ensured that the epilepsy/seizure service receives these referrals and sees the patients within a short time period; (4) a simple system is developed and implemented to allow continuous monitoring of key indices of epilepsy care.